Secondary pregnancy by an implant in a laparoscopic trocar site: A case report. Issue 18 (May 2018) - Ma, Zhihua; Zhao, Lanbo; Xu, Na; Sun, Chao; Wang, Qi; Wang, Yueling; Li, Qiling; Lu, Qinrui
Abstract: Rationale: For nearly 20 years, laparoscopy has been generally regarded as the gold standard for the surgical treatment of ectopic pregnancy and its application is very widespread. According to our knowledge, secondary pregnancy at the laparoscopic trocar site has not yet been reported until now. Patient concerns: A 24-year-old Chinese female patient is reported herein. Her left fallopian tube was removed via laparoscopy due to a first ectopic pregnancy. Her postoperative blood β-human chorionic gonadotropin (β-hCG) was increasing with irregular vaginal bleeding. The patient was initially regarded as having an old ectopic pregnancy. Diagnoses: Secondary pregnancy by an implant in a laparoscopic trocar Site. Interventions: Because of secondary pregnancy at the laparoscopic port site, laparoscopic surgery was performed again 32 days after the first operation. Approximately 1000 milliliters (mL) of free intraperitoneal hemorrhage and active bleeding of the lesion were detected. Histopathologic examination confirmed the lesion was the result of pregnancy with visible villous tissue. Outcomes: Her blood β-hCG gradually declined to a normal range in 28 days after the second operation. Menstruation occurred on day 20 after the second operation, and the duration and quantity were normal. Lessons: Although laparoscopy has many advantages, secondary pregnancy at the laparoscopic trocar port wound caused the patient enormous physical and mental pain and increased the medical costs. The etiology of secondary ectopic pregnancy at the laparoscopic puncture site was mainly an iatrogenic factor. Therefore, the procedure should be standardized to avoid its occurrence. Abstract : Supplemental Digital Content is available in the text